“I Still Love my Country”: Supporting the Social Integration of Recent Immigrant-Origin Students Through Drawing and Philosophical Dialogue - Fowler, Ellen (Comparative and International Education / Éducation comparée et internationale)

(untitled) (University of Western Ontario, 2025)
This article explores the potential of Philosophy for Children (P4C) to support the social integration of first- and second-generation immigrant students. It presents a portion of the results of a study that took place in 2023 in a Montréal primary school. The results, based on students’ drawings, philosophical dialogues conducted with the class, and interviews with the students and their teacher, suggest that P4C activities combining drawing with group dialogue can enable immigrant-origin students to explore questions related to identity and belonging and to make connections between their experiences and those of other students. Based on these results, I propose that the Ministry of Education integrate P4C activities incorporating creative expression into the pedagogical approaches recommended for supporting the integration of recent immigrant-origin students in Quebec.